Clinical functional MRI of the language domain in children with epilepsy - Wilke, Marko (Hum Brain Mapp, 2010)
Functional MRI (fMRI) for the assessment of language functions is increasingly used in the diagnostic workup of patients with epilepsy. Termed “clinical fMRI,” such an approach is also feasible in children who may display specific patterns of language reorganization. This study was aimed at assessing language reorganization in pediatric epilepsy patients, using fMRI. We studied 26 pediatric epilepsy patients (median age, 13.05 years; range, 5.6–18.7 years) and 23 healthy control children (median age, 9.37 years; range, 6.2–15.4 years), using two child‐friendly fMRI tasks and adapted data‐processing streams. Overall, 81 functional series could be analyzed. Reorganization seemed to occur primarily in homotopic regions in the contralateral hemisphere, but lateralization in the frontal as well as in the temporal lobes was significantly different between patients and controls. The likelihood to find atypical language organization was significantly higher in patients. Additionally, we found significantly stronger activation in the healthy controls in a primarily passive task, suggesting a systematic confounding influence of antiepileptic medication. The presence of a focal cortical dysplasia was significantly associated with atypical language lateralization. We conclude that important confounds need to be considered and that the pattern of language reorganization may be distinct from the patterns seen in later‐onset epilepsy. Hum Brain Mapp, 2011. © 2010 Wiley‐Liss, Inc.